CORRELATION OF METABOLIC AND ANTHROPOMETRIC PARAMETERS WITH PHYSICAL ACTIVITY AND SMOKING STATUS OF STUDENTS OF THE UNIVERSITY IN TUZLA - Edina Kuduzović; Edin Muftić; Azra Kurtić; Adela Jahić (Human Research in Rehabilitation, 2019)
Reduced physical activity and an increase in sedentary habits, as one of the factors in the development of cardiovascular diseases, hypertension, type 2 diabetes mellitus and other diseases, are also present in the youth population. The increasing of sedentary lifestyle and the reducing of physical activity can have negative consequences for the health of both genders, including increasing the risk of cardiovascular diseases (CVD). It is believed that almost 50% of young people do not practice regular physical activity. Regular physical activity reduces the risk in adults of early death caused by coronary heart disease, high blood pressure, type 2 diabetes mellitus, colon and breast cancer and depression. Studies investigating the sedentary lifestyle of young people in the United States show that the length of watching TV is directly proportional to the frequency of obesity. Daily moderate (medium-intensity) physical activity is beneficial for all people, regardless of age. The World Health Organization, within its "Health for All" strategy for the region of Europe, has set the goal for young people to be healthier and more capable to fulfill their roles in society in the year 2020 and that the psycho-social condition of people needs to be improved and help and service should be available to them, which will be better able to include and be more accessible to people with a mental health problem.